Serum TSH levels are associated with cardiovascular risk factors in overweight and obese adolescents - Luciana Lopes de Souza; Erika Paniago Guedes; Patrícia Fátima dos Santos Teixeira; Rodrigo Oliveira Moreira; Amelio Fernando Godoy‐Matos; Mario Vaisman (Brazilian Society of Pediatrics, 2016)
Objective: To investigate the relationship between serum thyrotropin (TSH), insulin resistance (IR), and cardiovascular risk factors (CRF) in a sample of overweight and obese Brazilian adolescents. Methods: A retrospective, longitudinal analysis of 199 overweight and obese pubescent adolescents was performed. The TSH and free T4 (fT4) levels, anthropometric measurements, and laboratory test results of these patients were analyzed. Results: 27 individuals (13.56%) presented with TSH levels above the normal level (subclinical hypothyroidism [SCH]). Their waist circumference (WC) was significantly higher than those of euthyroid individuals. Serum TSH was positively correlated with the homeostasis model assessment of insulin resistance (HOMA‐IR) index, triglycerides (TG) and high‐density lipoprotein cholesterol (HDL‐C). Using TSH and BMI as independent variables, TSH levels were shown to be independently related to HOMA‐IR (p = 0.001) and TG (p = 0.007). Among euthyroid subjects, individuals with TSH values < 2.5 mIU/mL exhibited statistically significant decreases in waist‐to‐hip ratio, HDL‐C levels, and HOMA‐IR scores and a tendency towards lower WC values. Conclusion: SCH in overweight and obese adolescents appears to be associated with excess weight, especially visceral weight. In euthyroid adolescents, there appears to be a direct relationship between TSH and some CRF. In conclusion, in the present sample of overweight and obese adolescents, TSH levels appear to be associated with IR and CRF.